2000
DOI: 10.1002/etc.5620190918
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker response and health of polychlorinated biphenyl‐ and chlordane‐contaminated paddlefish from the Ohio River Basin, USA

Abstract: Abstract-Fifty paddlefish (Polyodon spathula) collected from two sites on the Ohio River and from one site on the Cumberland River, USA, were examined to determine gonad polychlorinated biphenyl (PCB) and chlordane concentrations, amounts of plasma sex steroids (testosterone and estradiol), hepatic microsomal ethoxyresorufin-O-deethylase (EROD) activity, and the presence of immunoreactive cytochrome P450 1A (CYP1A) protein. Percent hatch and liver, spleen, and kidney histology were also determined. Gonad PCB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
5
15
0
Order By: Relevance
“…In laboratory exposures of freshwater fish, the lowest heptachlor and heptachlor epoxide residue concentrations associated with adverse effects are several orders of magnitude greater than levels present in the 1995 samples (Jarvinen and Ankley 1999), but there are no data for chlordane. Paddlefish (Polyodon spathula) eggs from the Ohio River collected in 1997 contained 0.35 g/g of chlordane and 0.74 g/g of PCBs (Gundersen et al 2000), similar to levels observed in the 1995 samples from the OHR subbasin ( Figure 6). The testes of male Ohio River paddlefish contained fourfold greater concentrations and possible contaminant-related effects on the adult fish, but not on hatching success, were noted (Gundersen et al 2000).…”
Section: Chlordane and Heptachlorsupporting
confidence: 62%
See 1 more Smart Citation
“…In laboratory exposures of freshwater fish, the lowest heptachlor and heptachlor epoxide residue concentrations associated with adverse effects are several orders of magnitude greater than levels present in the 1995 samples (Jarvinen and Ankley 1999), but there are no data for chlordane. Paddlefish (Polyodon spathula) eggs from the Ohio River collected in 1997 contained 0.35 g/g of chlordane and 0.74 g/g of PCBs (Gundersen et al 2000), similar to levels observed in the 1995 samples from the OHR subbasin ( Figure 6). The testes of male Ohio River paddlefish contained fourfold greater concentrations and possible contaminant-related effects on the adult fish, but not on hatching success, were noted (Gundersen et al 2000).…”
Section: Chlordane and Heptachlorsupporting
confidence: 62%
“…Environmental concentrations of organochlorine pesticides, polychlorinated biphenyls (PCBs), and other persistent environmental contaminants have generally declined over the last two decades (Schmitt and Bunck 1995;Schmitt et al 1999c;Gundersen et al 2000). In North America and elsewhere the release of many such contaminants to the environment has been reduced or eliminated through regulation and replacement by shorter-lived, less toxic compounds.…”
mentioning
confidence: 99%
“…Conversely, this observation with females is consistent with results of previous studies with teleosts that have reported impairments in males, but not in females, after exposure to certain contaminants either in the laboratory (Lema et al, 2008;Muirhead et al, 2006) or in the field (Patiño et al, 2003). In adult fishes, one reason that females may be less sensitive to contaminant exposures than males may be their ability to eliminate lipophilic contaminants via eggs released during spawning (Gundersen et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Fish health may be affected by a variety of environmental contaminants including polybrominated biphenyl ethers (PBDEs; Arkoosh et al, 2010;Muirhead et al, 2006), polychlorinated biphenyls (PCBs; Gundersen et al, 2000), dichlorodiphenyltrichloroethane metabolites (DDTs; Slaninova et al, 2009), polyaromatic hydrocarbons (PAHs; Johnson et al, 2008), and heavy metals (Golovanova, 2008). However, little is known about the effects that these contaminants have on the status of fish populations, especially in regards to contaminant mixtures present in the river.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental concentrations of many persistent environmental contaminants have generally declined over the last two decades (Schmitt and Bunck, 1995;Schmitt et al, 1999b;Gundersen et al, 2000), ostensibly as a result of environmental regu-lation. Nevertheless, there is a substantial body of information indicating that concentrations of organochlorine chemicals, mercury (Hg), and other persistent contaminants in fish may remain sufficiently elevated to harm fish and wildlife in some areas, and levels of some may be rising (e.g., Gooch and Matsamura, 1987;Colborn, 1991;Tillitt et al, 1992;Farag et al, 1994Farag et al, , 1995Schmitt and Bunck, 1995;Woodward et al, 1997;Yeardley et al, 1998;Schmitt, 1999Schmitt, , 2002aSchmitt et al, 1999bSchmitt et al, , 2002Stansley and Roscoe, 1999;Wildhaber et al, 2000;Brumbaugh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%